Process Optimization of Spark Plasma Sintering Parameters for Tungsten Carbide/Silicon Nitride/AA2219 Composites by Taguchi Method. (30th September 2022) - Althahban, Sultan; Pathinettampadian, Gurusamy; Qahtani, Faez; Jazaa, Yosef; Mousa, S.; Anjani Devi, Sanipina; De Poures, Melvin Victor; Subbiah, R.; Mamo, Hana Beyene
Abstract : It is usual practice to optimize the various processing parameters in order to achieve well-organized and lucrative process conditions. For the creation of tungsten carbide/silicon nitride/AA2219 composites, sintering temperature, sintering pressure, dwelling time, and heating rate all must be optimized. Design of experiments and analysis of variance were employed to assess the factors' contributions to density as well as microhardness response variables. It was decided to test the admixed powders and Vickers hardness tester, optical microscope, and Archimedes-based density testing to evaluate the sintered compacts. The optimum spark plasma sintering factors were a temperature of 500°C, a pressure of 30 MPa, a dwelling time of 8 minutes, and a heat rate of 160 °C/min, resulting in an extreme density of 2.71 g/cm 3 and a maximum microhardness of 38.61 HV (0.38 GPa).